1991
DOI: 10.1080/02652039109373974
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of sodium alginate in humans

Abstract: Following a 7-day control period, five male volunteers consumed a weight of sodium alginate corresponding to 175 mg/kg body weight for 7 days, followed by 200 mg sodium alginate per kg body weight for a further 16 days. Measurements before and at the end of the 23-day period of dietary supplementation showed that sodium alginate acted as a faecal bulking agent for all volunteers, giving a significant (p less than 0.01) increase in daily wet weight, and also increases in the water content and daily dry weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…As alginates are hydrocolloids that escape full bacterial fermentation, they are expected to greatly increase stool water content and bulk, as has been previously demonstrated (Anderson et al, 1991). They also appear to beneficially alter the colonic microflora (Terada et al, 1995) by increasing bifidobacterial numbers and reducing bacterial toxin levels in the colonic lumen.…”
Section: Direct Effects On Colonic Mucosamentioning
confidence: 84%
See 1 more Smart Citation
“…As alginates are hydrocolloids that escape full bacterial fermentation, they are expected to greatly increase stool water content and bulk, as has been previously demonstrated (Anderson et al, 1991). They also appear to beneficially alter the colonic microflora (Terada et al, 1995) by increasing bifidobacterial numbers and reducing bacterial toxin levels in the colonic lumen.…”
Section: Direct Effects On Colonic Mucosamentioning
confidence: 84%
“…Intake of 175-200 mg kg body weight −1 of alginate by male volunteers (n = 5) has previously been shown to increase stool wet and dry weight, but not decrease whole gut transit time (Anderson et al, 1991). Similar bulking of luminal products have also been reported in pigs fed a diet containing 5% alginate , and this effect was reported to be higher in the colon than other seaweed dietary fibres (i.e., cellulose, xylan, or carrageenan) of the same concentration.…”
Section: Bulking Of Colonic Contentsmentioning
confidence: 99%
“…A safety study of sodium alginate ingestion showed no adverse effects, other than a bulk laxative effect when taken in high doses over a prolonged period. 2 This method of nasogastric tube insertion requires appropriate preparation of the nose with local anaesthetic, together with appropriate alignment of the nasendoscope with the nasogastric tube.…”
Section: Discussionmentioning
confidence: 99%
“…Alginic acids, extracted from brown seaweeds or Phaeophyceae, are unbranched high‐molecular polymers containing two types of uronic acid residues of β‐(1 → 4)‐linked D ‐mannuronic acid and α‐(1 → 4)‐linked L ‐guluronic acid. Its derivatives have wide applications in various industries 21–24. We recently reported that monohydroxamates of aspartic acid and glutamic acid exhibit antioxidant and angiotensin‐converting enzyme inhibitory activities,25 and the pectin hydroxamic acids exhibited both semicarbazide‐sensitive amine oxidase and ACE inhibitory activities,26 and antioxidant activities 27.…”
Section: Introductionmentioning
confidence: 99%